UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MEMBUAT PERANGKAT PEMBELAJARAN MELALUI PENDAMPINGAN DI SMP NEGERI 2 PASIR LIMAU KAPAS KABUPATEN ROKAN HILIR - Aminudin ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study aims to determine whether the ability of teachers to create learning tools can beimproved through mentoring in SMP Negeri 2 Pasir Limau Kapas. The focus of this researchrelates to the ability of teachers to create learning tools can be improved through mentoringin SMP Negeri 2 Pasir Limau Kapas. This research is a classroom action research conductedin SMP Negeri 2 Pasir Limau Kapas. The research process is running in the supervision andmentoring principals. This is because this assistance is supporting the principal duty todetermine the ability of teachers to create learning tools can be improved through mentoringin SMP Negeri 2 Pasir Limau Kapas. This study was conducted by two cycles and time of thisstudy is one month. The results of this study revealed that the companion activity to improvethe ability of teachers to create learning tools has increased in each cycle. This statement issupported by the data obtained in the research which states that in the first cycle of 78.9% inboth categories and the second cycle increased to 87.8% in both categories.